STAR protocol for critically ill patients in Malaysia: ICU staff survey and human factor assessment - Razak A.A.; Abu-Samah A.; Razak N.; Suhaimi F.; Jamaludin U.; Ralib A.; Pretty C. (Institute of Electronics Engineers of Korea, 2023)
Human engineering; Patient treatment; Stars; Stochastic systems; Surveys; Critically-ill patients; Diabetes mellitus; Glycemic control; Insulin infusions; Metabolic variability; Model-based OPC; Protocol usage; Staff perceptions; Intensive care units